Spinal cord atypical teratoid/rhabdoid tumors in children: Clinical, genetic, and outcome characteristics in a representative European cohort. Issue 1 (1st October 2019) - Benesch, Martin; Nemes, Karolina; Neumayer, Petra; Hasselblatt, Martin; Timmermann, Beate; Bison, Brigitte; Ebetsberger‐Dachs, Georg; Bourdeaut, Franck; Dufour, Christelle; Biassoni, Veronica; Morales La Madrid, Andrés; Entz‐Werle, Natacha; et al.
Abstract: Background: Case reports have portrayed spinal cord atypical teratoid/rhabdoid tumor (spATRT) as an aggressive form of ATRT. We conducted a retrospective European survey to collect data on clinical characteristics, molecular biology, treatment, and outcome of children with intramedullary spATRT. Methods: Scrutinizing a French national series and the European Rhabdoid Registry database, we identified 13 patients (median age 32 months; metastatic disease at diagnosis, n = 6). Systemic postoperative chemotherapy was administered to all patients; three received intrathecal therapy and six were irradiated (craniospinal, n = 3; local, n = 3). Results: Median observation time was 8 (range, 1‐93) months. Progression‐free and overall survival rates at 1 and (2 years) were 35.2% ± 13.9% (26.4% ± 12.9%) and 38.5% ± 13.5% (23.1% ± 11.7%). Four patients (ATRT‐SHH, n = 2; ATRT‐MYC, n = 1; DNA methylation subgroup not available, n = 1) achieved complete remission (CR); two of them are alive in CR 69 and 72 months from diagnosis. One patient relapsed after CR and is alive with progressive disease (PD) and one died of the disease. Three patients (ATRT‐MYC, n = 2; subgroup not available, n = 1) died after 7 to 22 months due to PD after having achieved a partial remission ( n = 1) or stabilization ( n = 2). Five patients (ATRT‐MYC, n = 2; subgroup not available, n = 3) developed early PD and died. One patient (ATRT‐MYC) died of intracerebral hemorrhage prior to response evaluation. Conclusions: Long‐term survival is achievable in selected patients with spATRT using aggressive multimodality treatment. Larger case series and detailed molecular analyses are needed to understand differences between spATRT and their inracranial counterparts and the group of extradural malignant rhabdoid tumors.